1996
DOI: 10.1152/jappl.1996.81.5.2312
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall muscle cross talk in canine costal diaphragm electromyogram

Abstract: The present paper describes the influence of cross talk from the abdominal and intercostal muscles on the canine diaphragm electromyogram (EMG). The diaphragm EMG was recorded with bipolar surface electrodes placed on the costal portion of the diaphragm (abdominal side), aligned in the fiber direction, and positioned in a region with a relatively low density of motor end plates. The results indicated that cross talk may occur in the diaphragm EMG, especially during conditions of loaded breathing and light gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…Thus it may be difficult to thoroughly interpret the changes in CMAP characteristics. Previous studies had reported that CMAP amplitude and latency would be affected by different lung volumes [21,22]. We assumed both groups in our study were influenced to the same extent; however, the result showing significant difference of CMAP amplitude and latency could provide important information regarding the neuromuscular characteristics of inspiratory muscles in OSA patients.…”
Section: Study Limitationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus it may be difficult to thoroughly interpret the changes in CMAP characteristics. Previous studies had reported that CMAP amplitude and latency would be affected by different lung volumes [21,22]. We assumed both groups in our study were influenced to the same extent; however, the result showing significant difference of CMAP amplitude and latency could provide important information regarding the neuromuscular characteristics of inspiratory muscles in OSA patients.…”
Section: Study Limitationsmentioning
confidence: 78%
“…Use of intramuscular needle electrodes avoids cross-talk but contains disadvantages of invasiveness and sampling bias. sEMG recordings provide a popular, routine tool to investigate chest wall muscle function but can be confounded by noise and cross-talk [22]. This is a potential limitation of sEMG.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The use of surface electromyography to record respiratory muscle activity has been criticised because of difficulties in separating postural activity of the trunk muscles from that of the breathing muscles [14]. To minimise EMG contamination from the muscles of the trunk, all measurements were performed in the relaxed, upright seated position, with the patients' arms and trunk supported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the methodology that we used for acquisition and analysis of EAdi has been validated to address these problems (33). Contamination of EAdi by nondiaphragmatic activity occurs essentially when surface recording is used (31). Esophageal measurements of EAdi are less subject to contamination because the distance between electrodes and abdominal or intercostal muscles is greater (39).…”
Section: Discussionmentioning
confidence: 99%